A flexible rechargeable aqueous zinc manganese-dioxide battery working at −20 °C. Issue 2 (21st January 2019) - Mo, Funian; Liang, Guojin; Meng, Qiangqiang; Liu, Zhuoxin; Li, Hongfei; Fan, Jun; Zhi, Chunyi
Abstract : In this paper, we propose the design of a family of hydrogel electrolytes that featuring freezing resistance, flexibility, safety, superior ionic conductivity and long-term stability to realize anti-freezing flexible aqueous batteries. Abstract : It remains a challenge to render aqueous batteries operating at subzero temperatures properly, not even to mention the maintenance of their flexibility and mechanical robustness. This fundamentally arises from the freezing of hydrogel electrolytes under such low temperature, resulting in performance deterioration and elasticity loss. Here we propose an intrinsically freeze-resistant flexible zinc manganese-dioxide battery (Zn-MnO2 -B) comprising a designed anti-freezing hydrogel electrolyte which can preclude the ice crystallization of the hydrogel component and maintain a high ion conductivity even at −20 °C. Benefiting from exceptional freeze resistance, the fabricated anti-freezing Zn-MnO2 -B (AF-battery) exhibits excellent electrochemical stability and mechanical durability at subzero temperatures. Even at −20 °C, the specific capacity of the AF-battery can retain over 80% with Coulombic efficiencies approaching ∼100%, compared to the thorough performance failure of the Zn-MnO2 -B with traditional polyacrylamide (PAM) hydrogel electrolyte. More impressively, the flexibility of batteries can also be well maintained even under severe mechanical stresses at subzero temperatures, such as being bent, compressed, hammered or washed in an ice bath. Furthermore, the AF-battery sealed in an ice cube can be integrated in series to power a wristband of an electronic watch, LED lights and a 72 cm 2 electroluminescent panel. It is believed that this work opens new perspectives to develop anti-freezing batteries and would play the role of a model system for developing new hydrogel aqueous electrolytes for flexible batteries in extremely cold environments.